2021
DOI: 10.1088/1361-6463/ac18eb
|View full text |Cite
|
Sign up to set email alerts
|

Iron-based ferromagnetic van der Waals materials

Abstract: Two-dimensional magnets with high Curie temperatures have recently been produced by incorporating the prototypical ferromagnetic element, iron, into 2D van der Waals layers using the iron-based layered compounds known as Fe x GeTe2 (x = 3, 4, 5). In these materials, each layer consists of an Fe x Ge slab sandwiched by chalcogen tellurium (Te) atoms and the layers are stacked by van der Waals interactions. Their intrinsically high Curie temperatures, as high as room temperature, and large magnetization have dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Figure 1(e) shows the schematic of the 2D heterojunction based on vdWs materials. A series of 2D vdWs materials, such as Fe 3 GeTe 2 , MoS 2 and WSe 2 [37][38][39], exhibit promising characteristics with high coercivity, large TMR value and high PMA [40], which can be used to fabricate the promising MTJ device.…”
Section: Spintronics and Related Devicesmentioning
confidence: 99%
“…Figure 1(e) shows the schematic of the 2D heterojunction based on vdWs materials. A series of 2D vdWs materials, such as Fe 3 GeTe 2 , MoS 2 and WSe 2 [37][38][39], exhibit promising characteristics with high coercivity, large TMR value and high PMA [40], which can be used to fabricate the promising MTJ device.…”
Section: Spintronics and Related Devicesmentioning
confidence: 99%
“…In recent years, the rise of exploration and engineering in advanced 2D vdW materials, such as MoS 2 , WSe 2 , and Fe 3 GeTe 2 (FGT), and 2D vdW antiferromagnets, etc., has provided a new materials platform for further study of spintronics [15][16][17][18][19][20][21][22][23][24][25][26][27]. FGT has high-quality surfaces, large coercivity, and perpendicular magnetic anisotropy (PMA) [28]. In addition, more systematic studies have reported on the enhancement of the Curie temperature (T c ) of FGT [29][30][31] and the room temperature ferromagnetism of FGT with the gate modulation [32], ion doping [33,34], proximity coupling [35], exchange coupling effect [17], and atomic ratio engineering [36], demonstrating the excellent potential applications from the materials science and engineering performance perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, when FGT is the substrate, due to its buckled atomic structure, the interface coupling can modulated the energy gap at the edges of bilayer Bi(110) [44]. In short, there have been some researches on FGT properties [45] so far. However, constructing suitable FGT based heterostructures to improve its magneto-electronic properties and Curie temperature by interface effects and to expand its application potential still needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%